1999
DOI: 10.1111/j.1365-2621.1999.tb15117.x
|View full text |Cite
|
Sign up to set email alerts
|

Bifidobacterium longum Survival During Frozen and Refrigerated Storage as Related to pH during Growth

Abstract: Four strains of Bifidobacterium longum were grown at pH 5.5, 6.0, 6.5 and 7.0 and evaluated for survival and bile tolerance during frozen and subsequent refrigerated storage in milk. There were no reductions in cell numbers following initial freezing. There were effects for strain, pH and storage for three of the four strains of B. longum during storage at 58C in milk. Bifidobacterium longum S9 was more stable than other strains in that no losses occurred, regardless of pH during growth. Results were variable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 8 publications
0
13
0
Order By: Relevance
“…The use of a second reactor R2, with the first immobilized cell reactor R1, in series with a higher volume to increase biomass concentration in the effluent may not be a good strategy for promoting the growth of bifidobacteria in mixed cultures containing other competitive strains of lactic acid bacteria, like L. diacetylactis . However, the inhibitory conditions in R2 could also increase cell tolerance to various stresses, such as freeze‐drying or oxygen, that cells generally encounter following their production (17).…”
Section: Discussionmentioning
confidence: 99%
“…The use of a second reactor R2, with the first immobilized cell reactor R1, in series with a higher volume to increase biomass concentration in the effluent may not be a good strategy for promoting the growth of bifidobacteria in mixed cultures containing other competitive strains of lactic acid bacteria, like L. diacetylactis . However, the inhibitory conditions in R2 could also increase cell tolerance to various stresses, such as freeze‐drying or oxygen, that cells generally encounter following their production (17).…”
Section: Discussionmentioning
confidence: 99%
“…Usually, no growth is observed below 20 1C or above 46 1C. Optimal pH is between 6.5 and 7.0, with little or no growth below 5.0 or above 8.0 (Scardovi, 1986), but this appears to be strain-dependent since different studies have reported optimal growth in the pH range of 5.5-6.0 (Reilly & Gilliland, 1999;Doleyres, Paquin, LeRoy, & Lacroix, 2002b). A recently described phenotypic group, Bifidobacterium thermoacidophilum, differs from other species in its phenotypic characteristics, with some strains growing at thermophilic conditions (49.5 1C) and at relatively low pH (4.0) (Dong, Xin, Jian, Liu, & Ling, 2000;Zhu, Li, & Dong, 2003).…”
Section: Taxonomy and Growth Characteristicsmentioning
confidence: 96%
“…However, the maximum cell production (9 Â 10 8 cfu mL À1 ) was lower than in the high-cost MRS-cysteine medium (1.4 Â 10 9 cfu mL À1 ), which is commonly used in laboratory for bifidobacteria propagation. High bifidobacteria productions in MRS have been reported with four strains of B. longum, with average maximal cell concentrations of 3.3, 8.9, 3.7 and 1.3 Â 10 9 cfu mL À1 at pH 5.5, 6.0, 6.5, and 7.0, respectively (Reilly & Gilliland, 1999).…”
Section: Article In Pressmentioning
confidence: 98%
See 1 more Smart Citation
“…In the initial phase, probiotic cultures are selected based not only on the functional criteria but also on additional technological aspects including enhanced yields during cultivation at the industrial scale and improved survival during culture concentration and freeze drying. The selection of adequate strains and improvement of various technologies used in the preparation of probiotics are certainly (Carvalho et al, 2003;Reilly & Gilliland, 1999). Unfortunately, exposure to high acidity, substrate limitations and subsequently to low water activities and temperature (i.e., low during freezing or high during spray drying) leads to detrimental changes that may affect the culture survival and activity not only during cultivation but further application.…”
Section: Technological Challenges In the Development Of Probiotic Daimentioning
confidence: 99%